Telocytes Contribute as Cell Progenitors and Differentiation Inductors in Tissue Regeneration - Vannucchi, Maria-Giuliana; Bani, Daniele; Faussone-Pellegrini, Maria-Simonetta (Current Stem Cell Research & Therapy, 2016)
According to recent literature data, a peculiar connective tissue cell, called telocyte (TC), is present in almost all organs. Furthermore, TC subtypes, often coexisting in the same organ, but having different immunohistochemical and ultrastructural characteristics, have been demonstrated. Characteristically, TC, by connecting to each other and/or with other cell types, build three-dimensional networks. In the latter case they form a mixed network. TC, therefore, may be part of an integrated system to maintain tissue/organ function. Several roles have been proposed for the TC some of which support the importance of these cells in the differentiation and regenerative processes. Indeed, TC might behave as inductors/regulators of differentiation during morphogenesis due to their ability to release molecular signals and to construct the scaffold necessary for the parenchymal organization. In the adulthood, TC may be considered mesenchymal stromal cells able to differentiate in different cell types, such as the interstitial cells of Cajal, the resident myofibroblasts and the fibroblasts. Furthermore, the TC might be essential for the survival, proliferation, differentiation, maturation and guidance of the parenchymal stem cells located in the niches of several organs and, eventually, stimulate and sustain the regenerative processes.
Keywords: mesenchymal stromal cells